Multi-Band Analogue Electromagnetically Induced Transparency in DoubleTuned Metamaterials - Wei Huang (MDPI AG, 2021)
A multi-band analogue electromagnetically induced transparency (A-EIT) metamaterial is proposed. The structure is composed of liquid crystal (LC) layer and a graphene strips layer on both sides of silicon dioxide. The transmission spectrum and electric field distribution of only one graphene strip and two graphene strips have been studied. As a bright mode, the graphene strip is coupled with adjacent graphene strip to realize the A-EIT effect. When multiple graphene strips are coupled with each other, the multi-band A-EIT is obtained due to the electric dipole resonances of the four strips. The results show that the multiband A-EIT effect can be tuned by voltage on LC and graphene layer, respectively. Moreover, changing the incident angle of the electromagnetic wave has had little influence on the transmission window in the low frequency band, it is meaning that the A-EIT effect with insensitive to the incident angle can be obtained. Each transmission window has a high maximum transmittance and figure of merit (FOM). The multi-band A-EIT effect can widen the application on sensor and optical storage devices.